Estimation of Equivalent Series Resistance (ESR) of Supercapacitors Using Charging/Discharging Kinetics - Mohamed Y. Adel; Omar B. Mohammed; Ahmad T. Younis (ChemistryOpen)
Abstract One of the key parameters that affects efficiency, power density and performance of a supercapacitor (SC) is the equivalent series resistance (ESR). In this study we propose a method to estimate ESR from the charging kinetics which has practical applications. Therefore, to study the ESR of the SC we must look at the different factors that affect this resistance. In this study, the rise time extracted from the charging kinetics curves of the SC was used as an indirect method to investigate the ESR of the SC. Three different parameters were taken into account: ionic mobility, solvent material and pore cavity size of the porous electrode. The results offer enlightening information for optimizing the design of the SC with higher performance and smaller ESR values that will be translated into a better energy storage technologies.